2012
DOI: 10.3748/wjg.v18.i39.5533
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and clinical evidence of antioxidant therapy in acute pancreatitis

Abstract: Oxidative stress has been shown to play an important role in the pathogenesis of acute pancreatitis (AP). Antioxidants, alone or in combination with conventional therapy, should improve oxidative-stress-induced organ damage and therefore accelerate the rate of recovery. In recent years, substantial amounts of data about the efficiency of antioxidants against oxidative damage have been obtained from experiments with rodents. Some of these antioxidants have been found beneficial in the treatment of AP in humans;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 105 publications
(125 reference statements)
0
29
0
2
Order By: Relevance
“…Esrefoglu M. summarized experimental and clinical evidence of antioxidant therapy e.g ascorbic acid, alpha tocopherol, beta-carotene, melatonin, carnitine and N-acetyl-cysteine in cases of AP. Use of antioxidant regimens in the management of AP as a supplement and combined with conventional therapy are reasonable, but there are no sufficient data for using them alone 17 . Another study on rats showed an anti-inflammatory effect of pentoxifylline by inhibiting NF-κB activation in acute pancreatitis and pancreatic ischaemia-reperfusion (I-R) models.…”
Section: Treatment Of Underlying Disease (Sap)mentioning
confidence: 99%
See 2 more Smart Citations
“…Esrefoglu M. summarized experimental and clinical evidence of antioxidant therapy e.g ascorbic acid, alpha tocopherol, beta-carotene, melatonin, carnitine and N-acetyl-cysteine in cases of AP. Use of antioxidant regimens in the management of AP as a supplement and combined with conventional therapy are reasonable, but there are no sufficient data for using them alone 17 . Another study on rats showed an anti-inflammatory effect of pentoxifylline by inhibiting NF-κB activation in acute pancreatitis and pancreatic ischaemia-reperfusion (I-R) models.…”
Section: Treatment Of Underlying Disease (Sap)mentioning
confidence: 99%
“…In pancreatics acinar cells, induction of oxygen free radicals promote apoptosis whereas their inhibition leads to an increase in necrosis accompanied by reduced ATP (ref. 17 ). The apoptotic pathway is an active process requiring specific proteins, proteases (now called caspases).…”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, acute destructive pancreatitis provokes and deepens the formation of LPO and leads to significant violations of the balance of the prooxidative-antioxidative systems, as it was pointed out by the number of certain authors [10,12,13].…”
Section: Results and Discussion Of The Researchmentioning
confidence: 99%
“…Damaged acinar cells release AFO, LPO products that are able to activate neutrophils with subsequent potentiation of SIR and microcirculatory disorders. Unsatisfactory results of treatment and a high mortality rate in severe forms of AP are largely determined by complications and inadequately studied pathogenesis, as well as prediction of the course of pancreatic inflammation [13].…”
Section: Results and Discussion Of The Researchmentioning
confidence: 99%